Tumour regression and improved gastrointestinal tolerability from controlled release of SN-38 from novel polyoxazoline-modified dendrimers - England, Richard M.; Hare, Jennifer I.; Barnes, Jennifer; Wilson, Joanne; Smith, Aaron; Strittmatter, Nicole; Kemmitt, Paul D.; Waring, Michael J.; Barry, Simon T.; Alexander, Cameron; Ashford, Marianne B. (Elsevier, 2017)
Irinotecan is used clinically for the treatment of colorectal cancer; however, its utility is limited by its narrow therapeutic index. We describe the use of a generation 5 l-lysine dendrimer that has been part-modified with a polyoxazoline as a drug delivery vehicle for improving the therapeutic index of SN-38, the active metabolite of irinotecan. By conjugating SN-38 to the dendrimer via different linker technologies we sought to vary the release rate of the drug to generate diverse pharmacokinetic profiles. Three conjugates with plasma release half-lives of 2.5 h, 21 h, and 72 h were tested for efficacy and toxicity using a mouse SW620 xenograft model. In this model, the linker with a plasma release half-life of 21 h achieved sustained SN-38 exposure in blood, above the target concentration. Control over the release rate of the drug from the linker, combined with prolonged circulation of the dendrimer, enabled administration of an efficacious dose of SN-38, achieving significant regression of the SW620 tumours. The conjugates with 2.5 and 72 h release half-lives did not achieve an anti-tumour effect. Intraperitoneal dosing of the clinically used prodrug irinotecan produces high initial and local concentrations of SN-38, which are associated with gastrointestinal toxicity. Administration of the 21 h release dendrimer conjugate did not produce a high initial Cmax of SN-38. Consequently, a marked reduction in gastrointestinal toxicity was observed relative to irinotecan treatment. Additional studies investigating the dose concentrations and dose scheduling showed that a weekly dosing schedule of 4 mg SN-38/kg was the most efficacious regimen. After 4 doses at weekly intervals, the survival period of the mice extended beyond 70 days following the final dose. These extensive studies have allowed us to identify a linker, dose and dosing regimen for SN-38 conjugated to polyoxazoline-modified dendrimer that maximised efficacy and minimised adverse side effects.